Design and Construction of a Website-Based Animal Equipment Sales Information System - Suryaningrat, Suryaningrat (Institut Riset dan Publikasi Indonesia, 2024)
Selling pet supplies is an industry that continues to grow along with increasing public awareness of the needs of pets. To increase efficiency and accessibility in this business, this research aims to design and build a website-based information system for selling pet supplies. The system development method used includes user needs analysis, user interface design, system implementation, and functionality testing. Through this website, users can easily explore and buy various pet supplies such as food, toys and other accessories. This system is also equipped with inventory management and order tracking features to ensure item availability and customer satisfaction. With the adoption of web-based technology, it is hoped that this system can improve the user's shopping experience and help business owners manage pet equipment sales operations more efficiently. This research uses testing in the form of black box testing.